Root Surface Area of Permanent Mandibular Teeth in Patients with Anterior Open Bite Malocclusion: A CBCT Assessment - Sirivan, Theerapat; Kuharattanachai, Kachaphol; Jotikasthira, Dhirawat; Tripuwabhrut, Kanich (Naresuan University Journal: Science and Technology (NUJST), 2023)
A previous study reported that the root surface areas (RSA) of the maxillary central and lateral incisors were substantially smaller in patients with anterior open bite malocclusion. However, the RSA of permanent mandibular teeth in patients with anterior open bite malocclusion has never been explored. The objective of this study was to investigate the RSA of permanent mandibular teeth in patients with anterior open bite malocclusion. Cone-beam computed tomography (CBCT) images of permanent mandibular teeth were selected from sixteen patients with anterior open bite malocclusion and sixteen patients with an anterior normal overbite. Mimics research software was used to construct three-dimensional tooth models from the CBCT images. 3-Matic Research software was employed to calculate the RSA. An independent t-test (p < 0.05) was used to compare the RSA of each tooth type. From the permanent mandibular central incisor toward the permanent mandibular second premolar, the means of RSA were significantly lower in the anterior open bite group than in the anterior normal overbite group. Anterior open bite malocclusion may affect the RSA in all permanent mandibular teeth except in permanent mandibular molars. Keywords: Root surface area, Anterior open bite, Cone-beam computed tomography, Occlusal hypofunction, Orthodontic treatment